Smoothing Problem in Anticipating Scenario - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider a smoothing problem for stochastic processes satisfying stochastic differential equations with Wiener processes that may not have a semimartingale property with respect to the joint filtration.